Growth Pattern of Pancur Batu Sub District in Kabupaten Deli Serdang Base on Ecological approach - Farhan Bagas F (International Journal of Architecture and Urbanism, 2020)
Pancur Batu is one of the sub-districts in Deli Serdang. Before 1945 Pancur Batu was called Sinuan Bungan with the capital city of Arhnemia, but in 1952 it changed administratively under Deli Serdang district. An Area's growth pattern of an area is directly proportional to the development of the socio-cultural, economic, and political elements. Using Kecamatan Pancur Batu, Kabupaten Deli Serdang as a case study, this paper systematically introduces an ecological approach methodology. The growth pattern of the Pancur Batu sub-district is the result of history and through a long process. The Pancur Batu sub-district environmental development is influenced by several factors, such as politics, economy, socio-culture, and ecological carrying capacity. These factors have a significant influence between the environment and humans.